Low dielectric hollow glass microspheres and preparation method thereof

The existing technology is solved by removing metal oxide impurities in hollow glass microspheres through hydrochloric acid, citric acid pickling and chelating resin adsorption technology, and combining the dispersion treatment of polyamide polyamine epoxychlorohydrin oligomer and cellulose ether. The problem of affecting dielectric performance has achieved the preparation of hollow glass microspheres with low dielectric constant and low dielectric loss, with excellent compressive strength and density stability.

CN118184111BActive Publication Date: 2024-12-20ZHENGZHOU HOLLOWLITE MATERIALS CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202410291476.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2024-12-20
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

There are impurities such as iron and manganese in existing hollow glass microspheres, which affect their dielectric properties and are difficult to effectively reduce dielectric constant and dielectric loss.

Method used

The soluble substance is dissolved by hydrochloric acid and citric acid pickling, and the adsorption treatment is performed by chelating resin to remove free metal oxides in the glass powder, and dispersed with polyamide polyamine epoxychlorohydrin oligomer and cellulose ether. Form a pure glass powder to reduce the content of metal impurities and prepare low-dielectric hollow glass microspheres.

Benefits of technology

It significantly reduces the dielectric constant and dielectric loss of hollow glass microspheres, improves its compressive strength and density stability, with a dielectric constant between 1.4 and 1.6, a dielectric loss between 0.0023 and 0.0025, and a compressive crushing rate of less than 20%. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118184111B_ABST
    Figure CN118184111B_ABST
Patent Text Reader

Abstract

The present invention provides a low dielectric hollow glass microsphere and a preparation method thereof, the preparation method comprising the steps of glass block melting, water quenching and crushing, impurity removal, dispersion treatment, hollow spheroidization treatment and the like. The impurity removal step mainly dissolves soluble substances by pickling with hydrochloric acid and citric acid, and simultaneously uses chelating resin for multiple adsorption treatments to obtain pure glass powder; the dispersion treatment step is mainly to improve the dispersibility of the pure glass powder; thus, the preparation method provided by the present invention can effectively reduce the content of metal oxides such as iron, manganese, and sodium in the hollow glass microspheres finally obtained, thereby reducing the dielectric properties of the hollow glass microspheres and improving the strength of the hollow glass microspheres and the stability of physical parameters such as density and particle size. The true density of the low dielectric hollow glass microspheres obtained by the above method is 0.40 to 0.48 g / cm 3 , particle size D90 is 30-40μm, dielectric constant is 1.4-1.6, dielectric loss is 0.0023-0.0025, and the compressive crushing rate at 16000psi is less than 20%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a low-dielectric hollow glass microsphere and a preparation method thereof. Background Art

[0002] Hollow glass microspheres are specially processed glass microspheres, whose main component is borosilicate, with a general particle size of 10-250 μm and a wall thickness of 1-2 μm. Hollow glass microspheres have the characteristics of low density, high compressive strength, low dielectric constant, high resistivity, small thermal conductivity and thermal shrinkage coefficient. They can be used in the field of 5G communications to significantly reduce the dielectric constant of materials and can be used to regulate the dielectric properties of printed circuit boards.

[0003] Entering the 21st century, the communications industry has developed rapidly, the information capacity of communications products has gradually increased, and the signal processing speed has also been continuously improved. 5G communications are characterized by high frequency, high speed and short wavelength, and their signal diffraction ability and electromagnetic wave coverage ability are poor. This requires the dielectric constant and dielectric loss of the communication material substrate to be as low as possible to improve communication efficiency.

[0004] To this end, Chinese patent application CN 112479595A discloses a hollow glass microsphere and its preparation method and application. The preparation method of the hollow glass microsphere includes taking 45%-80% silicon dioxide, 5%-15% aluminum oxide, 10%-35% boron oxide, 0.1%-15% calcium oxide, 0.1%-7% magnesium oxide and 2%-10% titanium dioxide to form a mixed powder; in a non-polar gas atmosphere, the mixed powder is expanded and heat-insulated and shaped, and then cooled and formed to obtain a hollow glass microsphere, which can make the circuit substrate have a lower and more stable Dk and Df. This patent application does not use binary metal oxides in the main raw materials, which can avoid the adverse effects of metal ions in the binary metal oxides on the Dk and Df of the hollow glass microspheres.

[0005] In the actual production process, various metal oxide impurities, such as iron oxide and manganese oxide, will be introduced due to reasons such as raw materials and production equipment. At the same time, the sodium oxide in the glass material is highly active, and there will be some free sodium oxide components in the crushed material. These impurities will affect the dielectric properties of the glass microspheres. Summary of the invention

[0006] In view of this, the main purpose of the present invention is to provide a low dielectric hollow glass microsphere and a preparation method thereof, mainly by reducing the content of metal oxides such as iron and manganese in the existing hollow glass microspheres to reduce the dielectric properties of the hollow glass microspheres.

[0007] In order to achieve the above object, the present invention protects the following technical solutions:

[0008] A method for preparing low dielectric hollow glass microspheres comprises the following steps:

[0009] Glass block melting: melting the raw materials for preparing hollow glass microspheres to obtain glass blocks;

[0010] Water quenching and crushing: firstly, the glass block is subjected to water quenching treatment to obtain a water quenched material, and then the water quenched material is subjected to ball milling and crushing treatment to obtain a crushed material with a particle size D90 of 17 to 22 μm;

[0011] Impurity removal: firstly, the crushed material and hydrochloric acid are stirred and mixed to dissolve the free metal oxides therein, and then filtered to obtain hydrochloric acid pickled crushed material; the hydrochloric acid pickled crushed material and citric acid solution are stirred and mixed to further dissolve and remove the free ions therein to obtain citric acid pickled crushed material; firstly, the citric acid pickled crushed material and chelating resin solution are stirred and mixed to perform chelating adsorption treatment, and then separated and dried to obtain pure glass powder;

[0012] Dispersion treatment: firstly, uniformly dispersing the pure glass powder with the polyamide polyamine epichlorohydrin oligomer solution, cellulose ether and deionized water to form a dispersion liquid; then dehydrating and drying to obtain a dispersed powder;

[0013] Hollow spheroidization treatment: hollow spheroidization treatment is performed on the dispersed powder to obtain low dielectric hollow glass microspheres.

[0014] The glass block melting, water quenching and pulverizing and hollow spheroidization processing steps can all be achieved by using existing technologies.

[0015] Specifically, the step of melting the glass block may include: placing the raw materials for preparing the hollow glass microspheres in a muffle furnace for melting treatment to obtain a glass block, wherein the melting temperature is preferably 1400-1500°C, such as 1400°C, 1450°C, 1500°C, etc.; the melting time is preferably 5-10 hours.

[0016] The raw materials for preparing the hollow glass microspheres are a mixture of raw materials used in the prior art for preparing hollow glass microspheres. For example, the raw materials for preparing the hollow glass microspheres may include 60-70 parts by mass of quartz sand, 8-15 parts by mass of calcium carbonate, 10-18 parts by mass of boric acid, 12-20 parts by mass of sodium carbonate, 3-9 parts by mass of aluminum hydroxide, 2-3 parts by mass of barium carbonate, and 2.5-3.5 parts by mass of sodium nitrate. The purity of each raw material is as follows: the purity of quartz sand is 95% or more, the purity of calcium carbonate is 97% or more, the purity of sodium carbonate is 97% or more, the purity of boric acid is 99% or more, the purity of aluminum hydroxide is 99% or more, the purity of barium carbonate is 98% or more, and the purity of sodium nitrate is 99% or more.

[0017] The step of water quenching and crushing may include: first placing the glass block in deionized water to rapidly cool it down to obtain a water quenched material; and then using a ball mill to perform ball milling and crushing on the water quenched material to obtain the crushed material. The particle size of the crushed material is preferably D90 of 17 to 22 μm, and the particle size is more preferably D90 of 18 to 20 μm.

[0018] The main purpose of the impurity removal step is to remove free metal oxides such as iron and manganese in the glass block, so that the hollow glass microspheres obtained later have a smaller content of free metal ions such as iron and manganese. Therefore, in the process of removing impurities from the glass block, the step of obtaining the hydrochloric acid pickling crushed material may include: first adjusting the pH to 2-3 with hydrochloric acid, then mixing and stirring the crushed material at 20-30°C for 30-60 minutes, and then separating the crushed material to obtain the hydrochloric acid pickling crushed material.

[0019] The step of obtaining the citric acid pickled pulverized material may include: firstly mixing a citric acid solution with a pH value of 4 to 5 and the hydrochloric acid pickled pulverized material at 60 to 70° C. for 30 to 60 minutes, and then performing separation treatment to obtain the citric acid pickled pulverized material.

[0020] The chelating and adsorption treatment step is mainly to further adsorb free metal ions in the crushed material by means of the chelating resin, and may include: firstly stirring and mixing the chelating resin solution and the citric acid pickled crushed material at 20-30° C. for 30-60 min, then separating the crushed material by means of a vibrating screen, and drying the crushed material to obtain the pure glass powder. The chelating resin is preferably YKM105 or YKM106.

[0021] The polyamide polyamine epichlorohydrin oligomer solution is mainly prepared by the following method: adipic acid and diethylenetriamine are reacted at a molar ratio of 1.15:1.0 at 185-190° C. for 2-3 hours, 900% of the total weight of water is added and stirred evenly, epichlorohydrin with a molar amount of 110% to 115% of diethylenetriamine is added at 60-65° C., and the reaction is continued for 3-3.5 hours to obtain the polyamide polyamine epichlorohydrin oligomer solution.

[0022] The dispersibility of pure glass powder affects the physical properties of hollow glass microspheres, such as density, particle size and strength. The preparation of hollow glass microspheres is achieved through the liquefaction and hollow spheroidization process of glass powder under high temperature environment. In order to control the density and particle size of hollow glass microspheres and improve the strength of hollow glass microsphere products, the main purpose of the dispersion treatment step is to improve the dispersibility of pure glass powder, obtain dispersed powder with good dispersibility, and prevent mutual adhesion to form large balls during the ball forming process, thereby affecting the density, particle size and strength of the product. Preferably, the mass ratio of the pure glass powder, polyamide polyamine epichlorohydrin oligomer solution, cellulose ether and deionized water is 100: (3-5): (0.7-1.2): (350-450). The dehydration and drying step may include: filtering the dispersed liquid to obtain the dispersed powder.

[0023] The hollow spheroidization step may include: adding the dispersed powder into a spheroidization furnace for hollow spheroidization to obtain the low dielectric hollow glass microspheres; wherein the spheroidization temperature is preferably 1300-1400°C.

[0024] The invention also provides low dielectric hollow glass microspheres prepared by the preparation method.

[0025] Therefore, the low dielectric hollow glass microspheres provided by the present invention are mainly treated by using hydrochloric acid and citric acid to dissolve soluble substances, and simultaneously using chelating resin for adsorption to remove multiple metal oxide impurities introduced by raw materials and production equipment, thereby reducing the content of free metal oxides such as iron and manganese in the finally obtained hollow glass microspheres, thereby achieving the purpose of reducing the dielectric properties of the hollow glass microspheres.

[0026] The true density of the hollow glass microspheres prepared by the method provided by the present invention is 0.40-0.48 g / cm 3 , particle size D90 is 28~40μm, dielectric constant is 1.4~1.6, dielectric loss is 0.0023~0.0025, and the compressive crushing rate at 16000psi is less than 20%. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an optical microscope photograph of the hollow glass microspheres provided by Example 1 of the present invention (magnified 200 times). DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below through specific implementation methods.

[0029] Unless otherwise specified, the reagents and materials used in the present invention can be purchased through commercial channels. Among them, the purity of the raw materials in the following embodiments is: the purity of quartz sand is more than 95%, the purity of calcium carbonate is more than 97%, the purity of sodium carbonate is more than 97%, the purity of boric acid is more than 99%, the purity of aluminum hydroxide is more than 99%, the purity of barium carbonate is more than 98%, and the purity of sodium nitrate is more than 99%; the viscosity of the cellulose ether used in the following embodiments and comparative examples is 30,000.

[0030] The polyamide polyamine epichlorohydrin oligomer solution used in the following examples and comparative examples was prepared by the following method: adipic acid and diethylenetriamine were reacted at a molar ratio of 1.15:1.0 at 190° C. for 2 h, 900% of the total weight of water was added and stirred evenly, and then epichlorohydrin (110% of the molar amount of diethylenetriamine) was added at 60° C., and the reaction was continued for 3 h to obtain a polyamide polyamine epichlorohydrin oligomer solution.

[0031] Example 1

[0032] 1. Raw material configuration (weight parts)

[0033] Quartz sand 70

[0034] Calcium carbonate 15

[0035] Boric acid 18

[0036] Sodium carbonate 12

[0037] Aluminum hydroxide 9

[0038] Barium carbonate 2

[0039] Sodium nitrate 2.5

[0040] Preparation of raw materials: Mix the above raw materials evenly according to the proportion to obtain a raw material mixture;

[0041] 2. Glass Block Melting

[0042] The raw material mixture prepared in step 1 is placed in a furnace at 1480° C. and melted for 5 hours to obtain a glass block;

[0043] 3. Water quenching and crushing

[0044] First, the melted glass block in step 2 is placed in deionized water to rapidly cool it down to form a water-quenched material; then the water-quenched material is crushed using a ball mill to prepare a crushed material with a particle size D90 of 19 μm;

[0045] 4. Impurity Removal

[0046] First, adjust the pH to 2 with hydrochloric acid, mix and stir the crushed material obtained in step 3 at 20-30°C for 40 minutes to dissolve the free metal oxides in the solution, and then separate the crushed material; then adjust the pH value of deionized water to 5 with citric acid, mix and stir the crushed material at 65°C for 60 minutes to dissolve the free sodium ions, iron ions, etc. in the solution, and then separate the crushed material; then use YKM105 and deionized water to stir the crushed material at 20-30°C for 60 minutes, separate the crushed material with a vibrating screen, and dry it to obtain pure glass powder;

[0047] 5. Decentralized processing

[0048] The pure glass powder, polyamide polyamine epichlorohydrin oligomer solution, cellulose ether and deionized water in step 4 are uniformly mixed in a mass ratio of 100:4:0.8:400, and then filtered, dehydrated and dried to obtain a dispersed powder;

[0049] 6. Hollow spheroidization treatment

[0050] The dispersed powder was added into a spheroidizing furnace and spheronized at 1300°C to obtain hollow glass microspheres with a particle size D90 of 30 μm. The optical microscope photograph thereof is shown in FIG. Figure 1 shown.

[0051] Example 2

[0052] The present embodiment provides a low dielectric hollow glass microsphere and a preparation method thereof, which is basically the same as the preparation method of the low dielectric hollow glass microsphere provided in Example 1, with the main difference being that the water-quenched material in step “three, water quenching and crushing” of the present embodiment is crushed to prepare a crushed material with a particle size D90 of 18 μm, and the other process steps and parameters are the same, and the finally obtained hollow glass microspheres have a particle size D90 of 28 μm.

[0053] Example 3

[0054] 1. Raw material configuration (weight parts)

[0055] Quartz sand 60

[0056] Calcium carbonate 8

[0057] Boric acid 12

[0058] Sodium carbonate 15

[0059] Aluminum hydroxide 3

[0060] Barium carbonate 2.6

[0061] Sodium nitrate 3.5

[0062] Preparation of raw materials: Mix the above raw materials evenly according to the proportion to obtain a raw material mixture.

[0063] 2. Glass Block Melting

[0064] The raw material mixture prepared in step 1 is placed in a furnace at 1400° C. and melted for 10 hours to obtain a glass block;

[0065] 3. Water quenching and crushing

[0066] First, the melted glass block in step 2 is placed in deionized water to rapidly cool it down to form a water-quenched material; then the water-quenched material is crushed using a ball mill to prepare a crushed material with a particle size D90 of 22 μm;

[0067] 4. Remove impurities

[0068] First, adjust the pH to 3 with hydrochloric acid, mix and stir the crushed material obtained in step 3 at 20-30°C for 30 minutes to dissolve the free metal oxides in the solution, and then separate the crushed material; then adjust the pH value of deionized water to 4 with citric acid, mix and stir the crushed material at 68°C for 30 minutes to dissolve the free sodium ions, iron ions, etc. in the solution, and then separate the crushed material; then use YKM106 and deionized water to stir the crushed material at 25°C for 40 minutes, separate the crushed material with a vibrating screen, and dry it to obtain pure glass powder;

[0069] 5. Decentralized processing

[0070] The pure glass powder, polyamide polyamine epichlorohydrin oligomer solution, cellulose ether and deionized water in step 4 are uniformly mixed in a mass ratio of 100:3:0.7:350, and then filtered, dehydrated and dried to obtain a dispersed powder;

[0071] 6. Hollow spheroidization

[0072] The dispersed powder after dispersion treatment was added into a spheroidizing furnace for hollow spheroidization at 1350° C. to obtain hollow glass microspheres with a particle size D90 of 40 μm.

[0073] Example 4

[0074] 1. Raw material configuration (weight parts)

[0075] Quartz sand 65

[0076] Calcium carbonate 15

[0077] Boric acid 10

[0078] Sodium carbonate 20

[0079] Aluminum hydroxide 3

[0080] Barium carbonate 3

[0081] Sodium nitrate 2.5

[0082] Preparation of raw materials: Mix the above raw materials evenly according to the proportion to obtain a raw material mixture.

[0083] 2. Glass Block Melting

[0084] The raw material mixture prepared in step 1 is placed in a furnace at 1500° C. and melted for 8 hours to obtain a glass block;

[0085] 3. Water quenching and crushing

[0086] First, the melted glass block in step 2 is placed in deionized water to rapidly cool it down to obtain a water-quenched material; then the water-quenched material is crushed using a ball mill to prepare a crushed material with a particle size D90 of 20 μm;

[0087] 4. Remove impurities

[0088] First, adjust the pH to 3 with hydrochloric acid, mix and stir the crushed material obtained in step 3 at 20-30°C for 60 minutes to dissolve the free metal oxides in the solution, and then separate the crushed material; then adjust the pH value of deionized water to 4.5 with citric acid, mix and stir the crushed material at 60°C for 30 minutes to dissolve the free sodium ions, iron ions, etc. in the solution, and then separate the crushed material; then use YKM105 and deionized water to stir the crushed material at 30°C for 60 minutes, separate the crushed material with a vibrating screen, and dry it to obtain pure glass powder;

[0089] 5. Decentralized processing

[0090] The pure glass powder, polyamide polyamine epichlorohydrin oligomer solution, cellulose ether and deionized water in step 4 are uniformly mixed in a mass ratio of 100:5:1.2:450, and then filtered, dehydrated and dried to obtain a dispersed powder;

[0091] 6. Hollow spheroidization

[0092] The dispersed powder was added into a spheroidizing furnace for hollow spheroidization at 1400°C to obtain hollow glass microspheres with a particle size D90 of 36 μm.

[0093] Comparative Example:

[0094] Comparative Example 1 The citric acid washing and dissolving step in step 4 of Example 1 was removed, and the other steps were the same, and finally hollow glass microspheres with a particle size D90 of 31 μm were obtained.

[0095] Comparative Example 2: The YKM105 chelating resin in Example 1 was replaced with deionized water, and the other conditions were the same, and finally hollow glass microspheres with a particle size D90 of 30 μm were obtained.

[0096] In Comparative Example 3, the hydrochloric acid pickling and dissolving step in Example 1 was removed, and the other steps were the same, and finally hollow glass microspheres with a particle size D90 of 29 μm were obtained.

[0097] Comparative Example 4: In Example 1, step 4 "removing impurities" was completely removed, and the rest was the same, and finally hollow glass microspheres with a particle size D90 of 29 μm were obtained.

[0098] In Comparative Example 5, step 5 in Example 1 was removed, and the other steps were the same, and finally hollow glass microspheres with a particle size D90 of 58 μm were obtained.

[0099] Comparative Example 6: The polyamide polyamine epichlorohydrin oligomer solution in step 5 of Example 1 was removed, and the other conditions were the same, and the final particle size D90 was 49 μm.

[0100] Comparative Example 7: The cellulose ether in step 5 of Example 1 was removed, and the other conditions were the same, and the final particle size D90 was 42 μm.

[0101] The hollow glass microspheres prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were subjected to the following tests, and the test results are shown in Table 1. The dielectric constant and dielectric loss at a frequency of 10 GHZ were measured according to the current industry standards. The compressive strength (breakage rate at 16000 psi) of the prepared hollow glass microspheres was measured according to the gas pressure method, and the true density was tested by the gas replacement method; the particle size D90 of the crushed material and the finished product was measured by a laser particle size analyzer; and the iron and manganese content in the hollow glass microspheres was detected by a flame atomic absorption spectrophotometer.

[0102] Table 1 Test results of relevant parameters of hollow glass microspheres

[0103]

[0104] It can be seen from Table 1 that the true density of the hollow glass microspheres prepared in Examples 1 to 4 is 0.40 to 0.48 g / cm 3 , particle size D90 is 28-40 μm, dielectric constant is 1.4-1.6, dielectric loss is 0.0023-0.0025, and 16000psi compressive crushing rate is less than 20%. Therefore, the hollow glass microspheres provided in the embodiment of the present invention have a low dielectric constant, significantly lower dielectric loss, and higher compressive strength.

[0105] The data of Example 1 and Comparative Examples 1 to 4 show that metal impurities in the glass powder can be removed by hydrochloric acid pickling, citric acid pickling and chelating resin adsorption, so that the content of free iron and manganese ions in the hollow glass microspheres is reduced, thereby reducing dielectric loss.

[0106] The data of Example 1 and Comparative Examples 5 to 7 show that the hollow glass microspheres prepared by using polyamide polyamine epichlorohydrin oligomer and cellulose ether as the dispersion solution have good stability in density, particle size, compressive strength and other properties. This is mainly because: the dispersed powder formed by the dispersion treatment of pure glass powder has good dispersibility, so that the powder does not adhere to each other to form large balls during the spheroidization process, which is conducive to ensuring the stability of the density, particle size, compressive strength and other properties of the hollow glass microspheres; the more specific reason is that: the polyamide polyamine epichlorohydrin oligomer has a moderately small molecular weight, and it contains a highly polar amide bond that is easily adsorbed on the particle surface in the glass powder. At the same time, it has cations, so that the cations are evenly dispersed on the particle surface, and synergistically with cellulose ether, so that the particles are in a state of mutual repulsion, thereby improving the dispersibility of the pure glass powder, so that the dispersed powder has good dispersibility.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A method for preparing low dielectric hollow glass microspheres, comprising the steps of: Glass block melting: melting the raw materials for preparing hollow glass microspheres to obtain glass blocks; Water quenching and crushing: firstly, the glass block is subjected to water quenching treatment to obtain a water quenched material, and then the water quenched material is subjected to ball milling and crushing treatment to obtain a crushed material with a particle size D90 of 17 to 22 μm; Impurity removal: firstly, the crushed material and hydrochloric acid are stirred and mixed to dissolve the free metal oxides therein, and then filtered to obtain the hydrochloric acid pickled crushed material; The hydrochloric acid pickled powder and citric acid solution are stirred and mixed, and free ions therein are further dissolved to obtain citric acid pickled powder; the citric acid pickled powder and chelating resin solution are stirred and mixed to perform chelating adsorption treatment, and then separated and dried to obtain pure glass powder; Dispersion treatment: firstly, uniformly dispersing the pure glass powder with the polyamide polyamine epichlorohydrin oligomer solution, cellulose ether and deionized water to form a dispersion liquid; then dehydrating and drying to obtain a dispersed powder; Hollow spheroidization treatment: hollow spheroidization treatment is performed on the dispersed powder to obtain low dielectric hollow glass microspheres; The polyamide polyamine epichlorohydrin oligomer solution is mainly prepared by the following method: adipic acid and diethylenetriamine are reacted at a molar ratio of 1.15:1.0 at 185-190°C for 2-3 hours, 900% of the total weight of water is added and stirred evenly, epichlorohydrin with a molar amount of 110% to 115% of diethylenetriamine is added at 60-65°C, and the reaction is continued for 3-3.5 hours to obtain a polyamide polyamine epichlorohydrin oligomer solution.

2. The preparation method according to claim 1, characterized in that The step of obtaining the hydrochloric acid pickled pulverized material comprises: first adjusting the pH to 2-3 with the hydrochloric acid, then mixing and stirring the pulverized material at 20-30° C. for 30-60 min, and then separating the pulverized material to obtain the hydrochloric acid pickled pulverized material.

3. The preparation method according to claim 1 or 2, characterized in that The step of obtaining the citric acid pickled crushed material comprises: firstly mixing a citric acid solution with a pH value of 4 to 5 and the hydrochloric acid pickled crushed material at 60 to 70° C. for 30 to 60 minutes, and then performing separation treatment to obtain the citric acid pickled crushed material.

4. The preparation method according to claim 3, characterized in that The chelating adsorption treatment step includes: firstly stirring and mixing the chelating resin solution and the citric acid pickled powder at 20-30° C. for 30-60 min, then separating the powder by using a vibrating screen, and drying to obtain the pure glass powder.

5. The preparation method according to claim 4, characterized in that: The chelating resin is YKM105 or YKM106.

6. The preparation method according to claim 1, characterized in that The mass ratio of the pure glass powder, the polyamide polyamine epichlorohydrin oligomer solution, the cellulose ether and the deionized water is 100: (3-5): (0.7-1.2): (350-450).

7. The preparation method according to claim 6, characterized in that: The dehydration and drying step includes: filtering the dispersed liquid to obtain the dispersed powder.

8. The preparation method according to claim 1 or 2 or 4 or 5 or 6 or 7, characterized in that: The hollow spheroidization treatment step comprises: adding the dispersed powder into a spheroidization furnace, and performing hollow spheroidization at 1300-1400° C. to obtain the low dielectric hollow glass microspheres.

9. The preparation method according to claim 1, characterized in that: The step of melting the glass block comprises: placing the raw materials for preparing the hollow glass microspheres in a muffle furnace and melting them at 1400-1500° C. to obtain the glass block.

10. The preparation method according to claim 9, characterized in that The melting time is 5 to 10 hours.

11. The preparation method according to claim 1 or 2 or 4 or 5 or 6 or 7 or 9 or 10, characterized in that: The raw materials for preparing the hollow glass microspheres include, by weight, 60-70 parts of uniformly mixed quartz sand, 8-15 parts of calcium carbonate, 10-18 parts of boric acid, 12-20 parts of sodium carbonate, 3-9 parts of aluminum hydroxide, 2-3 parts of barium carbonate and 2.5-3.5 parts of sodium nitrate.

12. The preparation method according to claim 11, characterized in that: The step of water quenching and crushing comprises: firstly placing the glass block in deionized water to rapidly cool it down to obtain a water quenched material; and then using a ball mill to perform ball milling and crushing treatment on the water quenched material to obtain the crushed material.

13. The preparation method according to claim 12, characterized in that The particle size D90 of the crushed material is 18-20 μm.

14. Low dielectric hollow glass microspheres prepared by the preparation method according to any one of claims 1 to 13.

15. The low dielectric hollow glass microsphere according to claim 14, characterized in that: Its true density is 0.40~0.48g / cm 3 , particle size D90 is 28~40μm, dielectric constant is 1.4~1.6, dielectric loss is 0.0023~0.0025, and the compressive crushing rate at 16000psi is less than 20%.

Citation Information

Patent Citations

  • Hollow glass microspheres as well as preparation method and application thereof

    CN112479595A

  • Preparation method of hollow porous micron order silicon spheres, silicon-based cathode material and lithium ion battery

    CN104538585A

  • Hollow glass bead and preparation method thereof

    CN104891804A

  • Method for removing impurities from high-purity quartz sand

    CN106186667A

  • Method for manufacturing hollow glass microspheres from waste glass

    CN106630615A